Bilateral parotitis in a patient under continuous positive airway pressure treatment - Abdullayev,Ruslan (2016)
Abstract Background and objectives: Many conditions such as bacterial and viral infectious diseases, mechanical obstruction due to air and calculi and drugs can cause parotitis. We present a case of unusual bilateral parotitis in a patient under non-invasive continuous positive airway pressure (CPAP) therapy for chronic obstructive pulmonary disease exacerbation in intensive care unit. Case report: A 36-year-old patient was admitted to intensive care unit with the diagnosis of chronic obstructive pulmonary disease exacerbation. Antibiotherapy, bronchodilator therapy and non-invasive positive pressure ventilation were applied as treatment regimen. Painless swellings developed on the 3rd day of admission on the right and a day after this on the left parotid glands. Amylase levels were increased and ultrasonographic evaluation revealed bilateral parotitis. No intervention was made and the therapy was continued. The patient was discharged on the 6th day with clinical improvement and regression of parotid swellings without any complications. Conclusions: Parotitis may have occurred after retrograde air flow in the Stensen duct during CPAP application. After the exclusion of possible viral and bacteriological etiologies and possible drug reactions we can focus on this diagnosis.